The Prevalence, Level of Knowledge and Methods of Providing Nutritional Supplements among Females Participating in Private Sports Clubs in the City of Ardabil, Iran - Babak Nakhostin-Roohi; Mansoor Asadi (International Journal of Nutrition Sciences, 2018)
Background: The use of nutritional supplements among athletes is sharply increasing. There are many investigations demonstrating side effects of dietary supplement use such as cardiovascular, hematological, metabolic, and neurological problems. The aim of this study was to assess prevalence, level of knowledge and methods of providing nutritional supplements among females attending in private sport clubs in the city of Ardabil, Iran. Methods: Seventy-three fitness private clubs in four municipalities were considered as the population of the study. According to Morgan's table, 163 people were chosen as a sample of 18 clubs in a multi-stage, randomized fashion. Structured interview was conducted by physical education students as interviewer using researcher-made questionnaires. The questionnaire included 19 questions and 4 sections. Results: Totally, 31.3% of participants used nutritional supplements. Vitamins (31.4%) and fat burners (27.5%) were the most commonly used supplements. More than half of the participants started supplementation with their instructor's suggestion (55.6%). Most participants who used nutritional supplements, believed that the use of supplements did not pose any risk (62.7%), while the majority of those who did not consume; believed it would be risky (73.2%). Furthermore, 50.9%of participants who did not take nutritional supplements believed supplementation would be harmful to health. Conclusion: The prevalence of nutritional supplements was high in non-professional females who did exercise for recreation or health promotion in private sport clubs. Since that many of these supplements were recommended by instructors and club owners, the main goal of selling these supplements seems to increase the income rather than their positive effects.